SUMOylation of PHYTOCHROME INTERACTING FACTOR 3 promotes photomorphogenesis in Arabidopsis thaliana. Issue 4 (28th November 2020) - Bernula, Péter; Pettkó‐Szandtner, Aladár; Hajdu, Anita; Kozma‐Bognár, László; Josse, Eve‐Marie; Ádám, Éva; Nagy, Ferenc; Viczián, András
Summary: In Arabidopsis thaliana, phytochrome B (phyB) is the dominant receptor of photomorphogenic development under red light. Phytochrome B interacts with a set of downstream regulatory proteins, including PHYTOCHROME INTERACTING FACTOR 3 (PIF3). The interaction between PIF3 and photoactivated phyB leads to the rapid phosphorylation and degradation of PIF3 and also to the degradation of phyB, events which are required for proper photomorphogenesis. Here we report that PIF3 is SUMOylated at the Lys13 (K13) residue and that we could detect this posttranslational modification in a heterologous experimental system and also in planta . We also found that the SUMO acceptor site mutant PIF3(K13R) binds more strongly to the target promoters than its SUMOylated, wild‐type counterpart. Seedlings expressing PIF3(K13R) show an elongated hypocotyl response, elevated photoprotection and higher transcriptional induction of red‐light responsive genes compared with plantlets expressing wild‐type PIF3. These observations are supported by the lower level of phyB in plants which possess only PIF3(K13R), indicating that SUMOylation of PIF3 also alters photomorphogenesis via the regulation of phyB levels. In conclusion, whereas SUMOylation is generally connected to different stress responses, it also fine‐tunes light signalling by reducing the biological activity of PIF3, thus promoting photomorphogenesis.